One rifle lost - safety catch only! memories if life in RMC in the early sixties - Mohd. Nordin Hasan ([publisher not identified], 2003)
The idea of this "book" emerged out of the suggestion that we compile all the "favoured" anecdotes on life in the Royal Military College when the "Boys" of intake 1963 were together on that hill in Sungai Besi, a place they called a home away from home. Life then was not as laid back as one would like to think. The "Boys" were always involved in one activity or another, one mischief to the next!